A Study of 11C-Benzoate as a Radiopharmaceutical for Renal Imaging - Sun, Q.-X.; Ji, Q.-M.; Wang, Y.-C.; Zhang, J.; Shi, X.-C.; Wang, Y.; Zhau, Z.-T.; In, L.-X.; Ye, Y.-F.; Chen, S.-Y.; Fan, F.-S.; Gu, C.-J.; Zhang, L.-F.; Li, Y.-J.; Bao, H.-Q.; He, W.-Y. (Nuklearmedizin - NuclearMedicine, 1984)
11C-benzoic acid prepared in a radiochemical purity over 90% was studied radiopharmacologically in mice and rabbits. The uptake of 11C-benzoate in ICR mice increased quickly. The ratio of kidney uptake rate to that in other organs reached values between 9 and 55 with a maximum at 10 min after i.v. injection. Gamma camera imaging of rabbits showed that uptake in the kidneys began at 2 min after injection and that activity began to appear in the bladder 4 min later. Rabbits with left renal artery ligature showed no uptake in the left kidney but the right kidney was imaged to the same extent as that of a rabbit without artery ligature. The kidney imaging of 11C-benzoic acid may be a useful method for renal diagnosis.